Study and evaluation of optimum location deployment for environment adaptive applications. Issue 5 (3rd September 2022) - Yamato, Yoji
Abstract : Heterogeneous hardware other than a small-core central processing unit (CPU) such as a graphics processing unit (GPU), field-programmable gate array (FPGA), or many-core CPU is increasingly being used. However, to use heterogeneous hardware, programmers must have sufficient technical skills to utilise OpenMP, CUDA, and OpenCL. On the basis of this, I have proposed environment-adaptive software that enables automatic conversion, configuration, and high performance operation of once written code, in accordance with the hardware. However, although it has been considered to convert the code according to the offload devices, there has been no study where to place the offloaded applications to satisfy users' requirements of price and response time. In this paper, as a new element of environment-adapted software, I examine a method to calculate appropriate locations using the linear programming method. I confirm that applications can be arranged appropriately through simulation experiments when some conditions such as application type and users' requirements are changed. GRAPHICAL ABSTRACT: UF0001